1989
DOI: 10.1104/pp.91.4.1288
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidate Acyltransferase Activities in the Microsomes from Palm Endosperm, Maize Scutellum, and Rapeseed Cotyledon of Maturing Seeds

Abstract: Lysophosphatidate (LPA) acyltransferase (EC 2.3.1.51) in the microsomes from palm endosperm (Syagrus cocoides Martius), maize scutellum (Zea mays L.), and rapeseed cotyledon (Brassica napus L.) of maturing seeds were studied for their specificities toward the acyl moiety of the substrates lysophosphatidate and acyl coenzyme A (CoA). The LPA acceptor greatly influenced the acyl CoA specificity of the enzyme and vice versa. With 1-oleoyllysophosphatidate (LPA-18:1), the palm enzyme was equally active on oleoyl C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0
2

Year Published

1990
1990
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(37 citation statements)
references
References 21 publications
3
32
0
2
Order By: Relevance
“…Specifically, we have been studying the enzymes from different oilseed species to see if they can use short (lauric) and long (erucic)-chain acyl moieties in the substrates. In the study of LPA-AT in using substrates containing lauroyl moiety, we have found that the enzyme from palm kernel can use LPA-lauroyl and lauroyl CoA as the substrates, whereas those from other oilseed crops containing the normal C-16 and C-18 acyl moieties in seed TAG are unable to do so (10,15). This finding is consistent with the presence of lauroyl moiety in the sn-2 position of palm kernel Plant Physiol.…”
supporting
confidence: 75%
See 2 more Smart Citations
“…Specifically, we have been studying the enzymes from different oilseed species to see if they can use short (lauric) and long (erucic)-chain acyl moieties in the substrates. In the study of LPA-AT in using substrates containing lauroyl moiety, we have found that the enzyme from palm kernel can use LPA-lauroyl and lauroyl CoA as the substrates, whereas those from other oilseed crops containing the normal C-16 and C-18 acyl moieties in seed TAG are unable to do so (10,15). This finding is consistent with the presence of lauroyl moiety in the sn-2 position of palm kernel Plant Physiol.…”
supporting
confidence: 75%
“…We chose to study the substrate specificity (supplying one acyl acceptor and one acyl donor) rather than the substrate selectivity (supplying a mixture oftwo acyl acceptors and one acyl donor, and vice versa). The test ofspecificity is less stringent than the test ofselectivity in detecting substrate preference, as shown in the studies of LPA-AT from palm (10) and meadowfoam (to be described), and thus facilitates the detection of LPA-AT that can use substrates containing erucoyl moieties.…”
Section: Preparation Of Microsomesmentioning
confidence: 99%
See 1 more Smart Citation
“…coconut and meadowfoam microsomal LPATs. This last group might represent seed-specific LPATs that can acylate a unique acyl group to the sn-2 position of a TAG molecule (Kim and Huang, 2004), such as C-12 in coconut (Oo and Huang, 1989;Knutzon et al, 1995) and C-22:1 in meadowfoam (Cao et al, 1990;Hanke et al, 1995). Nevertheless, this last group also includes a rice LPAT derived from a genomic sequence, and rice seed TAG is not known to possess a unique acyl moiety at the sn-2 position.…”
Section: Arabidopsis Has Four Putative Cytoplasmic Atlpats That Can Bmentioning
confidence: 99%
“…A fascinating aspect of glycerolipid biosynthesis is that there often exists an asymmetric distribution of fatty acid (FA) molecules between the sn-1 and sn-2 positions: Saturated and monounsaturated FAs are normally found at sn-1, whereas polyunsaturated fatty acids (PUFAs) are enriched at sn-2. Pioneering work on plant acyltransferases has shown that GPATs and LPAATs are not only stereo-specific with regard to acylation of the glycerol backbone but also selective in terms of acyl-CoA donors (Griffiths et al, 1985;Ohlrogge and Browse, 1995;Oo and Huang, 1989;Bourgis et al, 1999;Kim and Huang, 2004;Kim et al, 2005). Therefore, the substrate specificity of the acyltransferases of the Kennedy pathway is one of the determining factors of the composition of glycerolipid molecules.…”
Section: Introductionmentioning
confidence: 99%